2002
DOI: 10.2169/internalmedicine.41.463
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hyalinizing Granuloma with Hydronephrosis

Abstract: A 49-year-old man was admitted for the evaluation of a bilateral mass shadow in his chest X-ray film. No definitive diagnosis was established either by brushing cytology or biopsy through bronchoscopy. No malignancies were suggested by general work-up. Both masses were surgically removed, and were diagnosed as pulmonary hyalinizing granuloma (PHG). Fifteen months later, low grade fever continued and the renal function decreased. Laboratory examinations revealed bilateral hydronephrosis with polyclonal hypergam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…4 Furthermore, there are a number of older reports in which PHG has been associated with lesions that have now been brought under the ISD umbrella, including sclerosing mediastinitis, retroperitoneal fibrosis, uveitis, and systemic idiopathic fibrosis. [5][6][7][8]22,23 Interestingly, our patient also had pleural fibrosis, which has been described as a thoracic manifestation of ISD. Our case is the first with a demonstration of increased serum and tissue IgG4 to specifically provide the link between PHG and ISD.…”
Section: Discussionmentioning
confidence: 75%
“…4 Furthermore, there are a number of older reports in which PHG has been associated with lesions that have now been brought under the ISD umbrella, including sclerosing mediastinitis, retroperitoneal fibrosis, uveitis, and systemic idiopathic fibrosis. [5][6][7][8]22,23 Interestingly, our patient also had pleural fibrosis, which has been described as a thoracic manifestation of ISD. Our case is the first with a demonstration of increased serum and tissue IgG4 to specifically provide the link between PHG and ISD.…”
Section: Discussionmentioning
confidence: 75%
“…Imatinib mesylate, a tyrosine kinase (TK) inhibitor, is approved for the treatment of chronic myeloid leukaemia and FIP1L1/PDGFRA positive gene fusion hypereosinophilia. A potential role for imatinib in the treatment of idiopathic hypereosinophilic syndrome (HES) [3] and AAV has been recently proposed [4,5].…”
Section: Disclosure Of Interestmentioning
confidence: 99%
“…The etiology and pathogenesis remain unclear, but most authors have hypothesized that patients with PHG show evidence of underlying autoimmune phenomena [2][3][4][5]. Gorini et al [6] reported the first case of pulmonary hyalinizing granulomas in which the patient had antineutrophil cytoplasmic autoantibodies with a granular cytoplasmatic pattern; they suggest that PHG could be regarded as a localized form of Wegener's granulomatosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The PHG can be combined with other diseases, e.g. with retroperitoneal fibrosis, but a pathophysiologic relation between these diseases has not been proven [3,4].…”
Section: Introductionmentioning
confidence: 99%